Átmenet a káoszból kozmoszba, avagy az apokalipszis reményt adó végkicsengése különös tekintettel a személyköztiségre - Szabó, Balázs (Kultúratudományi Szemle, 2022)
Transition from chaos to cosmos, or the hopeful ending of the apocalypse, especially with regard to interpersonalism Balázs Szabó Starting from a biblical approach, in this short paper I would like discuss a few thoughts with regard to the theme of apocalypse. I focus mostly on the relations of chaos and cosmos; hope; and last but not least, interpersonal structure. In my line of thought I would like to point out some crucial characteristics concerning the genre of apocalyptic literature. To be more specific, I seek to underline the distinctive paraenetic attributes of apocalyptic language in terms of a community that culminates in relevant personalist insights.